EXPLORING GAMIFICATION IN ENGLISH LANGUAGE TEACHING (ELT): ENHANCING MOTIVATION AND ENGAGEMENT IN LANGUAGE LEARNING - Nadia Safeer; Lubna Choudhry; Afsheen Kashifa (International Journal of Contemporary Issues in Social Sciences, 2024)
This research paper seeks to analyze the effects of gamification on increasing motivation and participation in English Language Teaching (ELT). Gaming of learning in which principles of games for example points, badges and leaderboards is incorporated in learning contexts has been widely embraced as a new way of developing engaging and fun language courses. Thus, more research is still required to determine its detailed influence in language acquisition and learners’ interaction in ELT settings. This study uses a combination of quantitative and qualitative research methods. This paper will be using survey data, pre- and post-tests, focus groups and interviews to determine the effects of different game aspects on learners’ motivation, participation and language ability over a 12-week period. Cross-cultural students and those with different English language learning levels will use an online platform to participate in ELT games. The research objectives are to determine the best gamification elements that would enhance the learner performance and to examine the cultural factors that may have an influence on the efficacy of gamified approaches. The findings of this study may be beneficial for educators, curriculum developers, and instructional designers to implement game elements into ELT to enable the students to learn a second language in a more meaningful and constructive manner. Moreover, the limitations of the study are pointed out and further research directions are proposed, such as, longitudinal studies and the investigation of particular language skills and learners’ characteristics.